+0  
 
0
47
3
avatar+347 

please help with question C 

thanks

YEEEEEET  Nov 7, 2018
 #1
avatar+91360 
+2

a)   (x - 2)^2  + (y - 1)^2   = 13        (1)

 

Second part.... expand (1)   and we have

 

x^2 - 4x + 4    + y^2 - 2y + 1  = 13     simplify

 

x^2 + y^2 - 4x - 2y  +  5   = 13       subtract 13 from both sides

 

x^2 + y^2 -4x - 2y - 8  =   0 

 

b)  A  = (4, k)

Sub 4 into (1)  for x

 

(4 - 2)^2  + ( y - 1)^2  = 13

2^2  + (y - 1)^2  = 13

4 + (  y - 1)^2  = 13

(y - 1)^2  = 9       take both roots

y - 1  = ±3

y =  ±3 + 1

So  y  =  3 + 1  = 4     or  y = -3 + 1  =  -2

 

So..... k  =  4     or k = -2

 

 

c) The tangent will meet the circle's radius at a  right angle...so...we have the right triangle ABC

AC will be one leg of the triangle  = sqrt (13)

BC will form the hypotenuse  = 7

And AB will form the other leg

 

So....using the Pythagorean Theorem

 

AB  =  sqrt  [  7^2  -  (sqrt (13) )^2  ]   = sqrt [ 49 - 13 ] = sqrt (36)  =  6

 

 

cool cool cool

CPhill  Nov 7, 2018
 #3
avatar+347 
+1

thank you very much!

YEEEEEET  Nov 7, 2018
 #2
avatar+116 
0

\(\sqrt{34}\)

Use the Pythagorean Theorem for it, \(BC\) is 7, and if we put a point \(D\) at \((4, 1)\),

 

\(DA = 3, DC = BC-DC = 7-2=5\)

The right angle is ADB, and \(AD^2+DB^2=AB^2, 3^2+5^2=AB^2, 34=AB^2, \sqrt{34}=AB\)

 

Therefore, \(AB = \sqrt{34}\)

 

You are very welcome!

:P

CoolStuffYT  Nov 7, 2018

12 Online Users

avatar

New Privacy Policy

We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive information about your use of our website.
For more information: our cookie policy and privacy policy.